2013
DOI: 10.1007/s12663-013-0526-3
|View full text |Cite
|
Sign up to set email alerts
|

Awareness About Needle Stick Injures and Sharps Disposal: A Study Conducted at Army College of Dental Sciences

Abstract: Background The present study aims to assess the knowledge and attitude about needle stick injuries and sharps disposal. Methods A self designed questionnaire of 15 questions was handed out to 200 participants including undergraduate students (group 1), postgraduate students (group 2), faculty members (group 3) and auxiliary staff members (group 4). The data was collected and analyzed using Chi square test. Results Sixty-one percent of total participants reported of experiencing needle stick injury and 25.5 % k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…Most of the events (66%) occurred while picking up the sharp from the floor which was in accordance with the study done by Bindra et al [4] where manipulation of sharps was found to be leading cause of NSIs. In other studies carried out among health care workers it was observed that most of the incidents occurred while recapping the needle [14,22,10].…”
Section: Discussion:-supporting
confidence: 90%
See 3 more Smart Citations
“…Most of the events (66%) occurred while picking up the sharp from the floor which was in accordance with the study done by Bindra et al [4] where manipulation of sharps was found to be leading cause of NSIs. In other studies carried out among health care workers it was observed that most of the incidents occurred while recapping the needle [14,22,10].…”
Section: Discussion:-supporting
confidence: 90%
“…According to a study done in medical students, it was found that 99.3% of the students had knowledge about Blood Borne disease [10]. Only 34% considered both HIV and Hepatitis being transferred by NSIs which was in accordance with previous studies [4,12]. But in a study done by MaqboolAlam in Saudi Arabia among nurses and paramedical staff, only 20% were not aware of both HIV and Hepatitis being transferred by NSIs [13] whereas study conducted by Muralidhar et al [14] among health care professionals found that almost all were aware of HIV and Hepatitis B and C being transferred by NSIs.…”
Section: Discussion:-supporting
confidence: 81%
See 2 more Smart Citations
“…Consequently, NSIs represent a serious health and safety concern for dental-HCWs. Similarly, other studies conducted in low- and middle-income countries have concluded that over half of dental-HCWs have been exposed to more than one NSI [ 22 , 23 , 54 ]. Furthermore, Jan et al [ 26 ] reported that participants had experienced multiple NSIs in the preceding 12 months, indicating that NSIs remain an ongoing, contemporary risk to dental-HCWs.…”
Section: Discussionmentioning
confidence: 70%